Mechanically reinforced starch-based film with near-infrared photothermal effect and its manufacturing method
Patent Information
- Application Number
- JP2023555294
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-10-26
- Filing Date
- 2023-02-17
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-02-17
AI Technical Summary
【0042】 [発明の効果] 本発明は、グラフェン界面におけるin-situ自己組織化と金属ポリフェノール配位反応とを組み合わせた二重コーティング方法に基づくものであり、温和な条件下で、4-メチルカテコールアミン系物質をπ-π共役効果によりグラフェン界面に吸着させ、アルカリ性自己重合反応によって4-メチルカテコールアミン系物質のグラフェン界面におけるin-situ層自己組織化を実現し、そして、金属ポリフェノール配位反応と組み合わせて、金属イオンと4-メチルカテコールアミン系ポリマーが金属ポリフェノールネットワークを形成するとともに、in-situでナノ粒子を形成して、グラフェン界面に親水基を分布させることにより、凝集を回避し、グラフェンの水性マトリックスでの分散性を向上させるとともに、該新規な複合澱粉ベースフィルムに安定かつ効率的な光熱変換性能と強化された機械的強度をもたらす。
Smart Images

Figure 0007642089000004 
Figure 0007642089000005 
Figure 0007642089000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a mechanically strengthened starch-based film with near-infrared photothermal effect and its manufacturing method, which belongs to the technical field of packaging material processing. [Background technology]
[0002] Sterilization methods used for conventional packaging materials mostly involve techniques such as external heating, ultraviolet irradiation, and radiation irradiation. However, these sterilization methods have problems such as a large energy loss in external heating, time-consuming ultraviolet irradiation, and complex equipment required for radiation irradiation, which is expensive and difficult to operate.
[0003] Near-infrared photothermal effect refers to the phenomenon that a material absorbs near-infrared light energy, converts the light energy into kinetic energy of electron resonance or hole resonance through surface plasmon resonance, or generates energy through electronic transition and transmits it to the surrounding environment, thereby increasing the environmental temperature. Materials with near-infrared photothermal effect can achieve the effect of killing bacteria, viruses and other microorganisms by generating heat through the excitation of near-infrared light, which can solve the sterilization problem of the above-mentioned traditional packaging materials.
[0004] Graphene has excellent properties such as excellent light-to-heat conversion efficiency and high thermal conductivity, making it highly likely to be applied to packaging for food, medicines, and medical devices.
[0005] Currently, graphene has been reported for use in packaging, for example:
[0006] (1) CN113372593A discloses a degradable graphene-based food packaging film and a manufacturing method thereof. In the invention, a degradable graphene-based food packaging film is obtained by strictly controlling the processing conditions. Although the added graphene powder can improve the decomposition rate of the packaging film, the tensile strength of the obtained food packaging film is only 5.14 MPa.
[0007] (2) CN112876710B relates to a biodegradable antibacterial graphene in-situ polymerized copolyester packaging film and its manufacturing process, the invention is for solving the bacteriostatic problem of sanitary material packaging, and mainly utilizes the bacteriostatic performance of graphene. The film contains 70-85 parts of hydroxy-type graphene oxide in-situ polymerized biodegradable copolyester, 5-20 parts of polylactic acid, 3-5 parts of inorganic filler, 0.1-1 part of antioxidant, 0.1-1 part of light stabilizer, and 0.1-1 part of lubricant, and has a tensile strength of up to 35.25 MPa.
[0008] (3) CN113604011A provides a method for producing a fully biodegradable graphene-based PBAT packaging bag, which is mainly used in daily life plastic shopping bags, etc., to address the problems existing in PBAT, such as low crystallinity, low melt tension, and high price.
[0009] (4) CN110343293A discloses a cellulose nanofiber / dopamine-reduced graphene oxide-reinforced starch film and a method for preparing the same. The mechanical properties of the starch film are improved mainly through the synergistic effect of dopamine-reduced graphene oxide and cellulose nanofiber, and the strength of the obtained starch film reaches 8.14 MPa.
[0010] (5) In addition, some literature has reported the use of graphene in packaging materials, which is either simply mixed or mixed after oxidative modification, mainly to solve the problems of mechanical strength and barrier performance of bio-based polymer packaging materials. The modification methods reported here have problems in that the conditions of the modification method are harsh and require energy consumption or the use of dangerous chemicals for production. For example, the oxidative modification of graphene requires harsh conditions such as high heat or oxidation with concentrated sulfuric acid (not a safe method). If the focus is only on improving mechanical properties and barrier properties without introducing photothermal conversion into the packaging material, even if graphene is used to impart bacteriostatic performance, the bacteriostatic performance is extremely weak.
[0011] In short, none of these reports are related to the utilization of the properties of graphene, such as photothermal conversion efficiency and high thermal conductivity, and the mechanical properties of the resulting packaging film must also be improved. Therefore, there is an urgent need to develop a mechanically reinforced biodegradable film material with near-infrared photothermal effect, which has important economic and social significance for the expansion of packaging sterilization technology, the extension of the shelf life of food and medicine, the prevention of microbial contamination, the improvement of the safety and quality of food and medicine, and the reduction of food waste. Summary of the Invention [Problem to be solved by the invention]
[0012] Biodegradable films containing graphene suffer from insufficient mechanical strength and lack of or unstable photothermal performance, limiting their applications.
[0013] Graphene is a hydrophobic material, and due to such characteristics, it is difficult to disperse uniformly in aqueous packaging materials, especially in biodegradable natural polymer matrices. As found by the present invention, this makes the photothermal effect of such packaging film materials unstable and prone to localized high heat, resulting in situations such as localized structure destruction, melting, and bursting of the film, making it difficult to actually apply it to packaging materials. [Means for solving the problem]
[0014] In order to solve the above problems, the present invention uses a double-coating method that combines in-situ self-organization at the graphene interface and metal polyphenol coordination reaction to prepare a mechanically reinforced starch-based film with near-infrared photothermal effect. The method of the present invention is simple, environmentally friendly, pollution-free, and has low energy consumption. Compared with pure starch-based films, the starch-based film prepared by the present invention has excellent photothermal conversion performance, and can be heated from 25°C to 103°C in 30s (seconds) and to 109°C in 1min (minutes) under near-infrared light irradiation, and has excellent mechanical properties, and the tensile strength is improved from 42MPa to 62MPa. The mechanically reinforced starch-based film with near-infrared photothermal effect prepared by the present invention can be used to expand packaging sterilization technology, extend the shelf life of food and medicine, prevent microbial contamination, improve the safety and quality of food and medicine, and reduce food waste, and can be used in particular for packaging food, medicine, or medical devices.
[0015] A first object of the present invention is to provide a method for producing a mechanically reinforced starch-based film with near-infrared photothermal effect, comprising the steps of: mixing and reacting a 4-methylcatecholamine-based substance solution with a graphene dispersion to obtain a graphene-4-methylcatecholamine-based composite material; then reacting the graphene-4-methylcatecholamine-based composite material with a metal ion solution to obtain a metal ion-modified graphene-4-methylcatecholamine-based composite material; dispersing the metal ion-modified graphene-4-methylcatecholamine-based composite material, and then uniformly mixing it with a starch gelatinization solution to obtain a film-forming liquid; and forming a film from the film-forming liquid to obtain a mechanically reinforced starch-based film with near-infrared photothermal effect.
[0016] In one embodiment, the method specifically comprises: (1) a step of in-situ self-organization of a 4-methylcatecholamine-based substance at a graphene interface, in which a 4-methylcatecholamine-based substance solution and a graphene dispersion are mixed and reacted with each other, and after the reaction is completed, the mixture is centrifuged, washed, and freeze-dried to obtain a graphene-4-methylcatecholamine-based composite material powder; (2) modifying the graphene-4-methylcatecholamine-based composite material with metal ions, by dispersing the graphene-4-methylcatecholamine-based composite material powder in water, adding a metal ion solution to react with the graphene-4-methylcatecholamine-based composite material powder, and then centrifugally washing and freeze-drying the graphene-4-methylcatecholamine-based composite material powder modified with metal ions; (3) preparing a film-forming liquid, the film-forming liquid being obtained by dispersing the metal ion-modified graphene-4-methylcatecholamine-based composite powder in water to obtain a dispersion liquid, and then uniformly mixing the dispersion liquid with a starch gelatinization solution to obtain a film-forming liquid; (4) A film-forming step, which comprises forming a film-forming liquid by a casting method to obtain the mechanically reinforced starch-based film having the near-infrared photothermal effect; Includes.
[0017] In one embodiment of the present invention, the 4-methylcatecholamine substance solution described in step (1) is obtained by dissolving a 4-methylcatecholamine substance in water, and has a concentration of 1 to 10 mg / mL.
[0018] In one embodiment of the present invention, the graphene dispersion described in step (1) is obtained by ultrasonically dispersing graphene in an alkaline buffer solution, and has a concentration of 1-10 mg / mL, the alkaline buffer solution comprises a PBS buffer solution having a pH of 7.5-10, the ultrasonic output is 90 W-120 W, and the ultrasonic time is 20-60 min.
[0019] In one embodiment of the present invention, the mass ratio of graphene to the 4-methylcatecholamine-based substance described in step (1) is 1:3 to 3:1.
[0020] In one embodiment of the present invention, the 4-methylcatecholamine substance described in step (1) includes one or more of 3,4-dihydroxyhydrocinnamic acid, 5,6-dihydroxyindole, L-dopamine, catecholamines, dopamine hydrochloride or dopamine.
[0021] In one embodiment of the present invention, the reaction described in step (1) is carried out at 600 to 900 rpm and 20 to 25° C. for 6 to 24 hours (hours).
[0022] In one embodiment of the present invention, the centrifugation described in step (1) has a rotation speed of 8,000 to 10,000 rpm and a time of 30 minutes, and the precipitate is removed by centrifugation and washed, and the washing is done with water.
[0023] In one embodiment of the present invention, the mass ratio of graphene-4-methylcatecholamine based composite powder to water in step (2) is 1:2.
[0024] In one embodiment of the present invention, the metal ion solution described in step (2) includes one or more of a copper sulfate solution, an iron chloride solution, a silver nitrate solution, or a zinc nitrate solution, and the concentration of the metal ion solution is 0.5 to 8 mg / mL.
[0025] In one embodiment of the present invention, the mass ratio of the graphene-4-methylcatecholamine-based composite material to the metal ion solution described in step (2) is 1:4 to 4:1.
[0026] In one embodiment of the present invention, the reaction described in step (2) is carried out at pH 7.5 to 9.5, 400 to 600 rpm, and 20 to 25° C. for 50 to 80 minutes.
[0027] In one embodiment of the present invention, the centrifugation described in step (2) has a rotation speed of 8,000 to 10,000 rpm and a time of 30 minutes, and the precipitate is removed by centrifugation and washed, and the washing is done with water.
[0028] In one embodiment of the present invention, the mass ratio of the metal ion modified graphene-4-methylcatecholamine based composite powder in step (3) to water is 1:1.
[0029] In one embodiment of the present invention, the dispersion described in step (3) is ultrasonic dispersion, the ultrasonic output is 90 W to 120 W, and the ultrasonic time is 20 to 60 minutes.
[0030] In one embodiment of the present invention, the method for preparing the starch gelatinizing solution described in step (3) comprises: Starch and water are mixed uniformly and then gelatinized to obtain a starch gelatinized solution. The dosage ratio of starch to water is 3g:80mL, and the gelatinization is carried out at 95°C for 10 minutes.
[0031] In one embodiment of the invention, the starch described in step (3) is one or more of corn starch, potato starch, wheat starch or sisal starch.
[0032] In one embodiment of the present invention, the mass ratio of starch to metal ion modified graphene-4-methylcatecholamine based composite powder in step (3) is 60:1 to 600:1.
[0033] In one embodiment of the present invention, the mass ratio of starch to metal ion modified graphene-4-methylcatecholamine based composite powder in step (3) is 100:1 to 300:1.
[0034] In one embodiment of the present invention, the homogeneous mixing described in step (3) refers to homogeneous mixing by stirring, and the stirring speed is 600 to 900 rpm.
[0035] In one embodiment of the present invention, the casting method described in step (4) involves injecting the film-forming liquid into a mold, drying it to form a film, and then removing and stabilizing the film, in which the drying method is hot air drying or vacuum drying, the drying temperature is 25 to 60°C, the drying time is 4 to 48 hours, and the stabilization conditions are a temperature of 22 to 37°C, a relative humidity of 50 to 80% RH, and a stabilization time of 12 to 72 hours.
[0036] A second object of the present invention is to provide a mechanically strengthened starch-based film with near infrared photothermal effect produced by the method according to the present invention.
[0037] The third object of the present invention is the use of the mechanically reinforced starch-based film with near-infrared photothermal effect according to the present invention in the fields of food, medicine, medical devices, agricultural products or textiles.
[0038] A fourth object of the present invention is to provide a packaging material comprising a mechanically strengthened starch-based film having near-infrared photothermal effect according to the present invention.
[0039] The fifth object of the present invention is to provide a degradable material comprising a mechanically reinforced starch-based film having near-infrared photothermal effect according to the present invention.
[0040] A sixth object of the present invention is to provide a medical material comprising a mechanically reinforced starch-based film having the near-infrared photothermal effect according to the present invention.
[0041] Medical materials include, but are not limited to, medical packaging materials and medical wound dressings.
[0042] [Effects of the invention] The present invention is based on a double-coating method combining in-situ self-organization at the graphene interface and metal polyphenol coordination reaction, in which 4-methylcatecholamine-based substances are adsorbed at the graphene interface through π-π conjugation effect under mild conditions, and 4-methylcatecholamine-based substances are realized to self-organize in-situ layers at the graphene interface through alkaline self-polymerization reaction. In combination with the metal polyphenol coordination reaction, metal ions and 4-methylcatecholamine-based polymers form a metal polyphenol network, and nanoparticles are formed in-situ, distributing hydrophilic groups at the graphene interface to avoid aggregation and improve the dispersibility of graphene in the aqueous matrix, and the novel composite starch-based film has stable and efficient photothermal conversion performance and enhanced mechanical strength.
[0043] The composite starch-based film prepared by the present invention is continuous and defect-free, and can be heated from room temperature to 100°C or higher within 0.5-1.5 minutes under near-infrared light irradiation, and has stable and efficient photothermal conversion performance, and has a tensile strength of 55-67 MPa, which is significantly stronger mechanical strength than that of pure starch films. In addition, data shows that the composite starch-based film prepared by the graphene-dopamine composite material modified with copper ions has a faster heating rate than that modified with iron ions, and the composite film modified with copper ions has remarkable antibacterial performance. It can be heated from 25°C to 103°C in as fast as 30 seconds and can be heated to 109°C in 1 minute, and the mechanical tensile strength of the corresponding composite film reaches 62 MPa. The composite starch-based film has excellent photothermal conversion performance and mechanical tensile strength, and can be used in the fields of packaging food, medicine, medical equipment, and agricultural products. [Brief description of the drawings]
[0044] [Figure 1]1 shows scanning electron micrographs of the copper ion modified graphene-dopamine composite in the photothermal effect mechanically reinforced starch-based film prepared in Example 1, the left photo has a scale bar of 10 μm and the right photo has a scale bar of 1 μm. [Diagram 2] 1 is a thermography photograph of the mechanically reinforced starch-based film with photothermal effect prepared in Example 1. [Diagram 3] 1 shows temperature-time curves of the composite starch-based films produced in Examples 1 to 4 and Comparative Examples 1 to 4 under near-infrared light irradiation. [Figure 4] 1 shows the mechanical tensile strength of the composite starch-based films prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 4. [Diagram 5] FIG. 2 shows the bacteriostatic performance of the composite starch-based films prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0045] Preferred examples of the present invention will now be described. However, it should be understood that the examples are provided to better illustrate the present invention and are not intended to limit the present invention.
[0046] The measurement method is as follows.
[0047] 1. Measurement of photothermal effect: The temperature change of the composite starch-based film under the excitation of near-infrared light is measured using a thermography analysis method to evaluate its photothermal effect.
[0048] The specific operating procedure is as follows: first, cut the film sample into a rectangular film with a length of 35 mm and a width of 8 mm; then, place the rectangular film 10 cm away from the near-infrared light source and use a thermography device to measure the temperature change of the rectangular film over time.
[0049] 2. Measurement of mechanical properties: Using a TA texture analyzer, a film tension method is set up to evaluate the tensile strength and tensile breaking elongation (tensile strength measured with the same mass of starch) of the composite starch-based film.
[0050] The specific measurement method is as follows: first, a film sample is left in a constant temperature and humidity environment of 53% humidity and 25°C temperature for 24 hours (hours); then, the film sample is cut into a long film of 80 mm length and 15 mm width; an A / TG film tensile tool is selected, the tensile test speed is set to 100 mm / min, and the gauge length is set to 40 mm; finally, the long film is fixed to the A / TG film tensile tool, and the tensile strength of the long film is measured and recorded.
[0051] The tensile strength is calculated according to the following formula: σ t =p / (bd) In the formula, p is the maximum load, the breaking load (N), b is the sample width (mm), d is the sample thickness (mm), and σ t is the tensile strength (MPa).
[0052] 3. Measurement of bacteriostatic performance: Using a UV-Vis spectrophotometer, the bacteriostatic performance of the composite starch-based film is evaluated based on the absorbance value of the bacterial solution at 600 nm.
[0053] The specific measurement method is as follows: 6 A CFU-containing E. coli liquid medium is prepared, 0.25 g of the composite starch-based film is added to 10 mL of E. coli liquid medium, the medium is incubated at 37°C for 24 h, and then the optical density of the medium corresponding to the bacterial growth at 600 nm spectrum is recorded using a UV-Vis spectrophotometer.
[0054] Example 1 The method for producing a mechanically reinforced starch-based film with near-infrared photothermal effect includes the following steps: Step (1), in-situ self-assembly of dopamine at the graphene interface: 40 mg of graphene is dispersed in 95 mL of PBS buffer solution with pH 8.5 by ultrasonic (100 W, 30 min) to obtain a graphene dispersion, 40 mg of dopamine is dissolved in 5 mL of water to obtain a dopamine solution, and then the dopamine solution and the graphene dispersion are mixed and reacted at 660 rpm and 25 °C for 24 h to obtain a crude dispersion of graphene-dopamine composite. Then, the crude dispersion of graphene-dopamine composite is centrifuged at 8000 rpm for 30 min to remove the precipitate, and water is added to wash by centrifugation, which is repeated three times, and freeze-dried to obtain the graphene-dopamine composite powder.
[0055] Step (2), modification of graphene-dopamine composite with copper ions: 40 mg of copper sulfate is added to 20 mL of water to obtain a copper sulfate solution. 40 mg of graphene-dopamine composite powder is dispersed in 80 mL of water, and then copper sulfate solution is added, the pH is adjusted to 8, and the mixture is reacted at 550 rpm and 25°C for 1 h to obtain a crude dispersion of graphene-dopamine composite modified with copper ions. The crude dispersion of graphene-dopamine composite modified with copper ions is then centrifuged at 8000 rpm for 30 min to remove the precipitate, and water is added to wash the precipitate by centrifugation, which is repeated three times, and then freeze-dried to obtain the above copper ion-modified graphene-dopamine composite powder.
[0056] Step (3): Preparation of film-forming solution: 20 mg of the copper ion-modified graphene-dopamine composite powder was dispersed in 20 mL of water by ultrasonic (100 W, 30 min) to obtain a dispersion, 3 g of corn starch was weighed and added to 80 mL of water, and gelatinized at 95°C for 10 min to obtain a starch gelatinized solution, and the dispersion and the starch gelatinized solution were uniformly stirred and mixed at 600 rpm to obtain a film-forming liquid.
[0057] Step (4) Film formation: Using the casting method, the film-forming liquid is poured into a polytetrafluoroethylene plate, placed in an oven at 40°C for 12 hours to dry, and then the film is peeled off and stabilized at a humidity of 53% for 24 hours to obtain a mechanically reinforced starch-based film (thickness 0.098 mm) with the above-mentioned photothermal effect.
[0058] Figure 1 shows a scanning electron microscope image of the graphene-dopamine composite modified with copper ions. As can be seen from Figure 1, the composite layer was coated on the graphene interface and successfully self-assembled in situ to form a nanoparticle layer.
[0059] FIG. 2 is a thermography photograph of the mechanically strengthened starch-based film with photothermal effect. As can be seen from FIG. 2, under near-infrared light irradiation, the thermography temperature of the starch-based film is 110° C., which proves that the starch-based film has photothermal effect.
[0060] Example 2: (NMS-GFe20) The method for producing a mechanically reinforced starch-based film with near-infrared photothermal effect includes the following steps:
[0061] Step (1), in-situ self-assembly of dopamine at the graphene interface: 40 mg of graphene is dispersed in 95 mL of PBS buffer solution with pH 8.5 by ultrasonic (100 W, 30 min) to obtain a graphene dispersion, 40 mg of dopamine is dissolved in 5 mL of water to obtain a dopamine solution, and then the dopamine solution and the graphene dispersion are mixed and reacted at 660 rpm and 25 °C for 24 h to obtain a crude dispersion of graphene-dopamine composite. Then, the crude dispersion of graphene-dopamine composite is centrifuged at 8000 rpm for 30 min to remove the precipitate, and water is added to wash by centrifugation, which is repeated three times, and freeze-dried to obtain the graphene-dopamine composite powder.
[0062] Step (2), modification of graphene-dopamine composite with iron ions: 40 mg of iron chloride hexahydrate is added to 20 mL of water to obtain an iron chloride solution. 40 mg of graphene-dopamine composite powder is dispersed in 80 mL of water, and then iron chloride solution is added, pH is adjusted to 8, and reacted at 550 rpm and 25°C for 1 h to obtain a crude dispersion of graphene-dopamine composite modified with iron ions. Then, the crude dispersion of graphene-dopamine composite modified with iron ions is centrifuged at 8000 rpm for 30 min to remove the precipitate, and water is added to wash by centrifugation, which is repeated three times, and freeze-dried to obtain the above graphene-dopamine composite powder modified with iron ions.
[0063] Step (3): Preparation of film-forming solution: 20 mg of the graphene-dopamine composite powder modified with iron ions was dispersed in 20 mL of water by ultrasonic (100 W, 30 min) to obtain a dispersion, 3 g of corn starch was weighed and added to 80 mL of water, and gelatinized at 95°C for 10 min to obtain a starch gelatinized solution, and the dispersion and the starch gelatinized solution were uniformly stirred and mixed at 600 rpm to obtain a film-forming liquid.
[0064] Step (4) Film formation: Using the casting method, the film-forming liquid is poured into a polytetrafluoroethylene plate, placed in an oven at 40°C for 12 hours to dry, and then the film is peeled off and stabilized at a humidity of 53% for 24 hours to obtain a mechanically reinforced starch-based film (thickness 0.098 mm) with the above-mentioned photothermal effect.
[0065] Example 3 The method for producing a mechanically reinforced starch-based film with near-infrared photothermal effect includes the following steps:
[0066] Step (1), in-situ self-assembly of dopamine at the graphene interface: 40 mg of graphene is dispersed in 95 mL of PBS buffer solution with pH 8.5 by ultrasonic (100 W, 30 min) to obtain a graphene dispersion, 40 mg of dopamine is dissolved in 5 mL of water to obtain a dopamine solution, and then the dopamine solution and the graphene dispersion are mixed and reacted at 660 rpm and 25 °C for 24 h to obtain a crude dispersion of graphene-dopamine composite. Then, the crude dispersion of graphene-dopamine composite is centrifuged at 8000 rpm for 30 min to remove the precipitate, and water is added to wash by centrifugation, which is repeated three times, and freeze-dried to obtain the graphene-dopamine composite powder.
[0067] Step (2), modification of graphene-dopamine composite with copper ions: 40 mg of copper sulfate is added to 20 mL of water to obtain a copper sulfate solution. 40 mg of graphene-dopamine composite powder is dispersed in 80 mL of water, and then copper sulfate solution is added, the pH is adjusted to 8, and the mixture is reacted at 550 rpm and 25°C for 1 h to obtain a crude dispersion of graphene-dopamine composite modified with copper ions. The crude dispersion of graphene-dopamine composite modified with copper ions is then centrifuged at 8000 rpm for 30 min to remove the precipitate, and water is added to wash the precipitate by centrifugation, which is repeated three times, and then freeze-dried to obtain the above copper ion-modified graphene-dopamine composite powder.
[0068] Step (3): Preparation of film-forming solution: 10 mg of the copper ion-modified graphene-dopamine composite powder was dispersed in 20 mL of water by ultrasonic (100 W, 30 min) to obtain a dispersion, 3 g of corn starch was weighed and added to 80 mL of water, and gelatinized at 95°C for 10 min to obtain a starch gelatinized solution, and the dispersion and the starch gelatinized solution were uniformly stirred and mixed at 600 rpm to obtain a film-forming liquid.
[0069] Step (4) Film formation: Using the casting method, the film-forming liquid is poured into a polytetrafluoroethylene plate, placed in an oven at 40°C for 12 hours to dry, and then the film is peeled off and stabilized at a humidity of 53% for 24 hours to obtain a mechanically reinforced starch-based film (thickness 0.089 mm) with the above-mentioned photothermal effect.
[0070] Example 4 The method for producing a mechanically reinforced starch-based film with near-infrared photothermal effect includes the following steps:
[0071] Step (1), in-situ self-assembly of dopamine at the graphene interface: 40 mg of graphene is dispersed in 95 mL of PBS buffer solution with pH 8.5 by ultrasonic (100 W, 30 min) to obtain a graphene dispersion, 40 mg of dopamine is dissolved in 5 mL of water to obtain a dopamine solution, and then the dopamine solution and the graphene dispersion are mixed and reacted at 660 rpm and 25 °C for 24 h to obtain a crude dispersion of graphene-dopamine composite. Then, the crude dispersion of graphene-dopamine composite is centrifuged at 8000 rpm for 30 min to remove the precipitate, and water is added to wash by centrifugation, which is repeated three times, and freeze-dried to obtain the graphene-dopamine composite powder.
[0072] Step (2), modification of graphene-dopamine composite with copper ions: 40 mg of copper sulfate is added to 20 mL of water to obtain a copper sulfate solution. 40 mg of graphene-dopamine composite powder is dispersed in 80 mL of water, and then copper sulfate solution is added, the pH is adjusted to 8, and the mixture is reacted at 550 rpm and 25°C for 1 h to obtain a crude dispersion of graphene-dopamine composite modified with copper ions. The crude dispersion of graphene-dopamine composite modified with copper ions is then centrifuged at 8000 rpm for 30 min to remove the precipitate, and water is added to wash the precipitate by centrifugation, which is repeated three times, and then freeze-dried to obtain the above copper ion-modified graphene-dopamine composite powder.
[0073] Step (3): Preparation of film-forming solution: 30 mg of the copper ion modified graphene-dopamine composite powder was dispersed in 20 mL of water by ultrasonic (100 W, 30 min) to obtain a dispersion liquid, 3 g of corn starch was weighed and added to 80 mL of water, and gelatinized at 95°C for 10 min to obtain a starch gelatinized solution, and the dispersion liquid and the starch gelatinized solution were uniformly stirred and mixed at 600 rpm to obtain a film-forming liquid.
[0074] Step (4) Film formation: Using the casting method, the film-forming liquid is poured into a polytetrafluoroethylene plate, placed in an oven at 40°C for 12 hours to dry, and then the film is peeled off and stabilized at a humidity of 53% for 24 hours to obtain a mechanically reinforced starch-based film (thickness 0.105 mm) with the above-mentioned photothermal effect.
[0075] Comparative example 1: (NMS-G) The method for producing the starch-based film includes the following steps.
[0076] Step (1), Preparation of graphene dispersion: Weigh out 5 mg of graphene and add it to 20 mL of deionized water, then sonicate at 100 W for 30 min until uniformly dispersed to obtain a graphene dispersion.
[0077] Step (2) Preparation of starch gelatinization solution: 3 g of corn starch is weighed out and placed in 80 mL of aqueous solution, and gelatinized at 95° C. for 10 minutes to obtain a starch gelatinized solution.
[0078] Step (3): Preparation of film-forming solution: The graphene dispersion and the starch gelatinization solution are uniformly mixed by stirring at 600 rpm to obtain a film-forming liquid.
[0079] Step (4) Film formation: Using the casting method, the film-forming liquid is poured onto a polytetrafluoroethylene plate, and then placed in an oven at 40°C for 12 hours to dry to form a film. The film is then peeled off and stabilized at 53% humidity for 24 hours to obtain the above starch-based film (thickness 0.085 mm).
[0080] Comparative Example 2 The method for producing a mechanically reinforced starch-based film with near-infrared photothermal effect includes the following steps:
[0081] Step (1), Preparation of graphene oxide dispersion: 20 mg of graphene oxide is dispersed in 20 mL of a PBS buffer solution with a pH of 8.5 using ultrasonic waves (100 W, 30 min) to obtain a graphene oxide dispersion.
[0082] Step (2): Preparation of film-forming solution: 3 g of corn starch is weighed and added to 80 mL of aqueous solution, and gelatinized at 95°C for 10 minutes to obtain a starch gelatinized solution. 20 mL of the graphene oxide dispersion and the starch gelatinized solution are uniformly stirred and mixed at 600 rpm to obtain a film-forming liquid.
[0083] Step (3) Film formation: Using the casting method, the film-forming liquid is poured onto a polytetrafluoroethylene plate, and then placed in an oven at 40°C for 12 hours to dry to form a film. The film is then peeled off and stabilized at 53% humidity for 24 hours to obtain a mechanically strengthened starch-based film (0.098 mm thick) with the above-mentioned photothermal effect.
[0084] Comparative example 3: (NMS-GCu5) The method for producing a mechanically reinforced starch-based film with near-infrared photothermal effect includes the following steps:
[0085] Step (1), in-situ self-assembly of dopamine at the graphene interface: 40 mg of graphene is dispersed in 95 mL of PBS buffer solution with pH 8.5 by ultrasonic (100 W, 30 min) to obtain a graphene dispersion, 40 mg of dopamine is dissolved in 5 mL of water to obtain a dopamine solution, and then the dopamine solution and the graphene dispersion are mixed and reacted at 660 rpm and 25 °C for 24 h to obtain a crude dispersion of graphene-dopamine composite. Then, the crude dispersion of graphene-dopamine composite is centrifuged at 8000 rpm for 30 min to remove the precipitate, and water is added to wash by centrifugation, which is repeated three times, and freeze-dried to obtain the graphene-dopamine composite powder.
[0086] Step (2), modification of graphene-dopamine composite with copper ions: 40 mg of copper sulfate is added to 20 mL of water to obtain a copper sulfate solution. 40 mg of graphene-dopamine composite powder is dispersed in 80 mL of water, and then copper sulfate solution is added, the pH is adjusted to 8, and the mixture is reacted at 550 rpm and 25°C for 1 h to obtain a crude dispersion of graphene-dopamine composite modified with copper ions. The crude dispersion of graphene-dopamine composite modified with copper ions is then centrifuged at 8000 rpm for 30 min to remove the precipitate, and water is added to wash the precipitate by centrifugation, which is repeated three times, and then freeze-dried to obtain the above copper ion-modified graphene-dopamine composite powder.
[0087] Step (3): Preparation of film-forming solution: 5 mg of the copper ion-modified graphene-dopamine composite powder was dispersed in 20 mL of water by ultrasonic (100 W, 30 min) to obtain a dispersion, 3 g of corn starch was weighed and added to 80 mL of water, and gelatinized at 95°C for 10 min to obtain a starch gelatinized solution, and the dispersion and the starch gelatinized solution were uniformly stirred and mixed at 600 rpm to obtain a film-forming liquid.
[0088] Step (4) Film formation: Using the casting method, the film-forming liquid is poured into a polytetrafluoroethylene plate, placed in an oven at 40°C for 12 hours to dry, and then the film is peeled off and stabilized at a humidity of 53% for 24 hours to obtain a mechanically reinforced starch-based film (thickness 0.081 mm) with the above-mentioned photothermal effect.
[0089] Comparative Example 4 The method for producing a mechanically reinforced starch-based film with near-infrared photothermal effect includes the following steps:
[0090] Step (1), in-situ self-assembly of dopamine at the graphene interface: 40 mg of graphene is dispersed in 95 mL of PBS buffer solution with pH 8.5 by ultrasonic (100 W, 30 min) to obtain a graphene dispersion, 40 mg of dopamine is dissolved in 5 mL of water to obtain a dopamine solution, and then the dopamine solution and the graphene dispersion are mixed and reacted at 660 rpm and 25 °C for 24 h to obtain a crude dispersion of graphene-dopamine composite. Then, the crude dispersion of graphene-dopamine composite is centrifuged at 8000 rpm for 30 min to remove the precipitate, and water is added to wash by centrifugation, which is repeated three times, and freeze-dried to obtain the graphene-dopamine composite powder.
[0091] Step (2): Preparation of film-forming solution: 20 mg of graphene-dopamine composite powder was dispersed in 20 mL of water by ultrasonic (100 W, 30 min) to obtain a dispersion liquid, 3 g of corn starch was weighed and added to 80 mL of water, and gelatinized at 95 °C for 10 min to obtain a starch gelatinized solution, and the dispersion liquid and the starch gelatinized solution were uniformly stirred and mixed at 600 rpm to obtain a film-forming liquid.
[0092] Step (3) Film formation: Using the casting method, the film-forming liquid is poured into a polytetrafluoroethylene plate, placed in an oven at 40°C for 12 hours to dry, and then the film is peeled off and stabilized at a humidity of 53% for 24 hours to obtain a mechanically reinforced starch-based film (thickness 0.094 mm) with the above-mentioned photothermal effect.
[0093] The performance measurements were carried out on the mechanically reinforced starch-based films having photothermal effect obtained in Examples 1 to 4 and the starch-based films obtained in Comparative Examples 1 to 4. The measurement results are shown in Figs. 3 to 5 and Tables 1 to 3, specifically as follows.
[0094] Figure 3 and Table 1 show the temperature-time change of each starch-based film under near-infrared light irradiation. As can be seen from Figure 3 and Table 1, in Example 1, after being stimulated with near-infrared light for 30 seconds, the temperature of the film reaches 100°C or more, proving that the graphene-dopamine composite modified with the added amount of copper ions plays a significant role in improving the photothermal effect of the starch-based film. In Example 2, after being stimulated with near-infrared light for 1 minute, the temperature can be raised from room temperature to 100°C, proving that the graphene-dopamine composite modified with the added amount of iron ions also plays a certain role in improving the photothermal effect of the starch-based film, but the temperature rise rate of Example 2 is slower than that of Example 1. The starch-based film of Example 3 takes 1 min to heat from room temperature to 100°C, proving that the graphene-dopamine composite modified with the added amount of copper ions plays a certain role in improving the photothermal effect of the starch-based film, but the graphene-dopamine composite modified with copper ions of Example 3 has a slower heating rate than that of Example 1 due to the reduced amount of copper ions added. The starch-based film of Example 4 takes 30 s to heat from room temperature to 100°C, proving that the graphene-dopamine composite modified with the added amount of copper ions plays a certain role in improving the photothermal effect of the starch-based film, but the heating rate of Example 4 is slower than that of Example 1, and the graphene-dopamine composite modified with the added copper ions has a large content, so when it is continuously stimulated by near-infrared light, the film becomes too hot and melts. The starch-based film of Comparative Example 1 took 1.5 minutes to heat from room temperature to 100°C, proving that the addition of graphene plays a certain role in improving the photothermal efficiency of the starch-based film, but its photothermal efficiency was lower than that of Example 1, and after reaching 100°C, the film melted and bent, and could not be measured, mainly due to the poor dispersion effect of graphene in the system. The starch-based film of Comparative Example 2 was gradually heated when irradiated with near-infrared light, but still did not reach 100°C after 1.5 minutes, proving that the addition of graphene oxide plays a certain role in improving the photothermal efficiency of the starch-based film, but its photothermal efficiency was lower than that of Example 1.The starch-based film of Comparative Example 3 was irradiated with near-infrared light, and the temperature gradually increased after 1.5 minutes, but still did not reach 100°C, proving that the graphene-dopamine composite modified with the added amount of copper ions plays a certain role in improving the photothermal effect of the starch-based film, but its photothermal effect is still lower than that of Example 1. The starch-based film of Comparative Example 4 was irradiated with near-infrared light, and the temperature gradually increased after 1.5 minutes, but still did not reach 100°C, proving that the addition of the graphene-dopamine composite plays a certain role in improving the photothermal effect of the starch-based film, but its photothermal effect is still lower than that of Example 1.
[0095] FIG. 4 and Table 2 show the mechanical properties of each starch-based film. As can be seen from FIG. 4 and Table 2, compared with Comparative Examples 1 to 4, the strength of the starch-based film of Example 1 is 62 MPa, proving that the film has a strong mechanical tensile strength. The tensile strength of the starch-based film of Example 2 is 56 MPa, proving that the addition of the graphene-dopamine composite modified with iron ions plays a significant role in enhancing the tensile strength of the starch-based film, but the strength is significantly lower than that of Example 1. The tensile strength of the starch-based film of Example 3 is 55 MPa, proving that the addition of the graphene-dopamine composite modified with 10 mg of copper ions plays a significant role in improving the tensile strength of the starch-based film. The tensile strength of the starch-based film of Example 4 is 67 MPa, proving that the addition of the graphene-dopamine composite modified with 30 mg of copper ions plays a significant role in enhancing the tensile strength of the starch-based film. The tensile strength of the starch-based film of Comparative Example 1 is 42 MPa, which proves that the addition of graphene plays a certain role in enhancing the tensile strength of the starch-based film, but the tensile strength is still lower than that of Example 1. The tensile strength of the starch-based film of Comparative Example 2 is 49 MPa, which proves that the addition of graphene oxide plays a certain role in enhancing the tensile strength of the starch-based film, but the tensile strength is still lower than that of Example 1. The tensile strength of Comparative Example 3 is 52 MPa, which proves that the tensile strength of the film is improved to a certain extent, but is lower than that of Example 1. The tensile strength of the starch-based film of Comparative Example 4 is 55 MPa, which proves that the addition of graphene-dopamine composite plays a certain role in enhancing the tensile strength of the starch-based film, but the tensile strength is still lower than that of Example 1.
[0096] FIG. 5 and Table 3 show the bacteriostatic performance of each starch-based film. As can be seen from FIG. 5 and Table 3, compared with the blank group, the pure starch film group, and Comparative Examples 1 to 3, the absorbance of the E. coli culture solution of Example 1 is 0.8, proving that the film has remarkable bacteriostatic performance against E. coli. The absorbance of the E. coli culture solution of the starch-based film of Example 2 is 1.09, proving that the film has a certain bacteriostatic activity, but it is weak. The absorbance of the E. coli culture solution of the starch-based film of Example 3 is 0.88, proving that the film has bacteriostatic activity, but it is still weak compared to Example 1. Meanwhile, the absorbance of the E. coli culture solution of the starch-based film of Example 4 is 0.78, proving that the film has bacteriostatic activity. Comparative Examples 1 to 4 have no bacteriostatic activity.
[0097] In summary, the methods of Examples 1-4 effectively improve the dispersibility of graphene in an aqueous matrix, provide the composite starch-based film with stable and efficient photothermal conversion performance, enhanced mechanical strength, and accelerate the heating rate. Specifically, the composite starch-based films prepared in Examples 1-4 can be heated from room temperature to above 100°C within 0.5-1.5 minutes under near-infrared light irradiation, and have stable and efficient photothermal conversion performance, as well as a tensile strength of 55-67 MPa, which is significantly enhanced mechanical strength compared to pure starch films. In addition, data shows that the composite starch-based film prepared by the graphene-dopamine composite material modified with copper ions has a faster heating rate than that modified with iron ions, and the composite film modified with copper ions has significant antibacterial performance.
[0098] In addition, in the composite material, it is preferable to control the mass ratio of starch to metal ion-modified graphene-4-methylcatecholamine-based composite powder within the range of 100:1 to 300:1. For example, if the amount of metal ion-modified graphene-4-methylcatecholamine-based composite added is too low, the photothermal conversion performance and enhanced mechanical strength will still be maintained, but the heating rate will be slow. Table 1: Temperature-time changes of starch-based films under near-infrared light irradiation TIFF0007642089000001.tif66170Table 2: Mechanical tensile strength of starch-based films TIFF0007642089000002.tif75170
[0099] The method for producing a pure starch film includes the following steps.
[0100] Step (1): Preparation of starch gelatinizing solution: 3 g of corn starch is weighed out and added to 100 mL of aqueous solution, and gelatinized at 95° C. for 10 minutes to obtain a starch gelatinized solution.
[0101] Step (2) Film formation: Using the casting method, the film-forming liquid was poured onto a polytetrafluoroethylene plate, and then the plate was placed in an oven at 40°C for 12 hours to dry it to form a film. The film was then peeled off and stabilized at a humidity of 53% for 24 hours to obtain the starch-based film (thickness 0.072 mm). Table 3: Antibacterial performance of starch-based films TIFF0007642089000003.tif77170
Claims
1. A method for producing a mechanically reinforced starch-based film having near-infrared photothermal effect, comprising: (1) performing in-situ self-organization of a 4-methylcatecholamine-based substance at a graphene interface, in which a 4-methylcatecholamine-based substance solution and a graphene dispersion are mixed and reacted with each other, and after the reaction is completed, the mixture is centrifuged, washed, and freeze-dried to obtain a graphene-4-methylcatecholamine-based composite material powder, in which the 4-methylcatecholamine-based substance is dopamine; (2) modifying the graphene-4-methylcatecholamine-based composite material with metal ions, in which the graphene-4-methylcatecholamine-based composite material powder is dispersed in water, and then a metal ion solution is added to react with the graphene-4-methylcatecholamine-based composite material powder; after the reaction is completed, the graphene-4-methylcatecholamine-based composite material powder is centrifuged, washed, and freeze-dried to obtain a graphene-4-methylcatecholamine-based composite material powder modified with metal ions, and the metal ion solution is a copper sulfate solution; (3) preparing a film-forming liquid, the metal ion-modified graphene-4-methylcatecholamine-based composite powder is dispersed in water to obtain a dispersion, and then the dispersion is uniformly mixed with a starch gelatinization solution to obtain a film-forming liquid, in which the mass ratio of starch in the starch gelatinization solution to the metal ion-modified graphene-4-methylcatecholamine-based composite powder is 100:1 to 300:1; (4) a film-forming step, in which the film-forming liquid is cast into a film to obtain the mechanically reinforced starch-based film having the near-infrared photothermal effect; A method comprising:
2. 2. The method of claim 1, wherein in step (1), the mass ratio of the graphene to the 4-methylcatecholamine-based substance is 1:3 to 3:
1.
3. 2. The method of claim 1, wherein in step (2), the mass ratio of the graphene-4-methylcatecholamine-based composite material to the metal ion solution is 1:4 to 4:
1.
4. 2. The method of claim 1, wherein in step (2), the concentration of the metal ion solution is 0.5 to 8 mg / mL.
5. Use of the mechanically reinforced starch-based film with near infrared photothermal effect according to any one of claims 1 to 4 in the fields of food production, medicine, medical devices, agricultural products or textiles.
Citation Information
Patent Citations
Cellulose nanofiber / dopamine reduced graphene oxide reinforced starch film and preparation method thereof
CN110343293A